Psychometric Properties and Confirmatory Factor Analysis of the Dark Tetrad Personality Questionnaire in Students - moslem ghobadiyan; mohammadjavad bagiyan; Tahereh Mahmoudiyan Dastnaee (مطالعات روانشناسی تربیتی)
Various attempts have been made to classify dysfunctional personality traits. Among these, the classification of dark three traits has attracted much attention over the past decade in the areas of social psychology and personality. The aim of this study was to evaluate the validity and reliability of comparing the Dark Tetrad Personality in a group of students aged 13 to 18 years. The research was conducted in the form of a correlational research project. The statistical population consists of all students aged 13 to 18 years in Khorramabad city in the academic year of 2019-2020. The research sample was 300 students (150 girls and 150 boys) of Khorramabad city who were selected by multi-stage cluster sampling method. Exploratory and confirmatory factor analysis were used to analyze the data using SPSS-26 and AMOS-21 software. The results showed that there was a positive and significant relationship between the components of the Dark Tetrad Personality and the Dark Tetrad of Jones and Webster (P≥0.001). The results of the exploratory factor analysis identified three factors that together explain 40.72% of the dark triple variance of personality. The results of the confirmatory factor analysis confirmed 24 items in three factors. Cronbach's alpha was 0.79 for the whole Dark Tetrad Personality questionnaire and 0.803 for the Machiavellian subscales, 0.78 for narcissism, and 0.68 for psychopathy. The Dark Tetrad Personality scale of personality has desirable psychometric properties in the Iranian student community.